2013
DOI: 10.1007/s12032-013-0782-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphism of CYP2B6 G15631T is associated with hematologic and cytogenetic response in chronic myeloid leukemia patients treated with imatinib

Abstract: In the spite of the impressive results achieved with imatinib in chronic myeloid leukemia (CML) patients, differences in patient's response are observed, which may be explained by interindividual genetic variability. It is known that cytochrome P450 enzymes play a major role in the metabolism of imatinib. The present study aimed to understand the functional impact of CYP2B6 15631G>T polymorphism on the response of imatinib in CML patients and its relation to CML susceptibility. We have genotyped CYP2B6 G15631T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The frequency of the CYP2B6 -rs3745274 mutant T allele observed in the Malian population was 37%, which is comparable to those observed in Central Africa (Cameroon 37%), [26] East Africa (Tanzania) 34%, [26] South Africa 36% [26] and in West African countries including Ivory Coast (38%), [27] Nigeria (36.3%), [28] and Ghana (46%) [29,30] . Looking at data from North Africa, we found that the frequency observed in Mali was statistically higher than that reported is Egypt (28.8%) P = .03, [31] but lower than that observed in the Moroccan population (55.5%) P = .000 [15] . As for CYP2B6- rs2279343, the frequency of the mutant G allele was 38% in the Malian population.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The frequency of the CYP2B6 -rs3745274 mutant T allele observed in the Malian population was 37%, which is comparable to those observed in Central Africa (Cameroon 37%), [26] East Africa (Tanzania) 34%, [26] South Africa 36% [26] and in West African countries including Ivory Coast (38%), [27] Nigeria (36.3%), [28] and Ghana (46%) [29,30] . Looking at data from North Africa, we found that the frequency observed in Mali was statistically higher than that reported is Egypt (28.8%) P = .03, [31] but lower than that observed in the Moroccan population (55.5%) P = .000 [15] . As for CYP2B6- rs2279343, the frequency of the mutant G allele was 38% in the Malian population.…”
Section: Discussionmentioning
confidence: 67%
“…[6][7][8] The human CYP450 superfamily consists of 18 families, 42 subfamilies with 59 active genes. [9] Among these, the CYP2B6 and CYP3A4 families have been widely explored in genetic association studies for multifactorial diseases such as gout, [10] acute myeloid leukemia, [11] chronic obstructive pulmonary disease [12] as well than in pharmacogenetic studies including antiretrovirals (nevirapine, efavirenz), [13] antimalarial (artemisinin), [14] anticancer (chronic myeloid leukemia) [15] and anesthetics (propofol). [16] The CYP2B6 and CYP3A4 genes are located on the long arms of chromosomes 19q13.2 and 7q22.1 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This was under the consideration that ABCB1 (P-glycoprotein), as an efflux transporter of imatinib, is highly expressed in intestinal epithelium and liver cells, influencing absorption and biliary elimination by pumping out xenobiotics [38]. All other genotypes were tested as potential covariates of CL because of their potential involvement in the metabolism of imatinib [39][40][41]. None of the potential demographic covariates (body weight, BMI, BSA and gender) showed a statistically significant association with the individual PK parameters.…”
Section: Discussion Poppk Model For Healthy Volunteersmentioning
confidence: 99%
“…In turn, homozygous patients with the CYP3A5 *3 genotype may experience reduced enzyme activity, leading to the limited clearance and high bioavailability of the drug, and the subsequent better response to IM, but also a possibly increased risk of adverse events. Another study which assessed the functional impact of CYP2B6 15631G/T polymorphism on the response of imatinib in CML patients demonstrated the relationship between a higher hematologic response and the presence of the 15631GG/TT genotype compared to 15631GT (36.8 vs. 13.8%; χ 2 = 3.542, p = 0.063) [ 210 ]. However, the complete cytogenetic response was better in patients carrying the 15631GG/GT genotype when compared with 15631TT (χ 2 = 3.298, p = 0.024), while the primary cytogenetic resistance was greater in those with the 15631GG/TT genotype when compared with 15631GT carriers (52.6 vs. 17.2%; χ 2 = 6.692, p = 0.010).…”
Section: The Impact Of Genetic Variations On Anticancer Treatment Eff...mentioning
confidence: 99%